ANALISIS PRAGMATIK TERHADAP STRATEGI KOMUNIKASI GURU DAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the communication strategies employed by teachers and students in Indonesian language learning at the elementary school level through a pragmatic approach. Classroom communication is not only a medium for delivering subject matter but also a means of fostering social interaction, character development, and language skills. By applying pragmatic analysis, this study focuses on speech acts, the cooperative principle, and politeness strategies that emerge during classroom interaction. The research employed a qualitative method, utilizing classroom observations, recorded conversations, and interviews with teachers and students from grades IV–VI of elementary school. Data were analyzed using pragmatic frameworks to identify types of speech acts and communication strategies used throughout the teaching and learning process. The findings reveal that teachers predominantly use directive speech acts, particularly in giving instructions, guidance, and reprimands, while students tend to respond with representative and expressive speech acts. Communication strategies observed include clarification, repetition, humor, and code-switching. Grice’s cooperative principle was generally adhered to, although some violations of the maxim of relevance were found in student interactions. In terms of politeness, teachers tended to apply positive politeness strategies to maintain interpersonal harmony with students. This study highlights that pragmatic analysis provides a deeper understanding of classroom communication dynamics. The findings imply the importance of enhancing teachers’ pragmatic competence in managing classroom interaction and underscore the need for Indonesian language learning at the elementary level to emphasize not only formal aspects but also contextual and communicative competence) Keywords: Pragmatics, Communication Strategies, Speech Acts, Teacher, Student, Indonesian Language Learning, Elementary School